Impak pembangunan pelancongan maritime ke atas sosioekonomi komuniti di Pulau Perhentian, Terengganu / Muhammad Faiz Ramli - Muhammad Faiz, Ramli (2016)
The development of the tourism industry is part of an effort to diversify the country's economic resources especially in the services sector so that the sector is becoming more dynamic, progressive and viable.However, maritime and island tourism among the most important form of tourism as it offers an attraction for tourists in terms of the beauty of the islands, environment, maritime resources, Marine Park, and also includes recreational activities such as scuba diving, snorkeling, jet ski down to the cruise (cruise ship).Therefore, the main focus of this research is to study the impact of marine tourism development on the socioeconomic of the local community at Pulau Perhentian, and also to analyze the role of government in developing maritime tourism on the island. Quantitative research method is used mainly through questionnaires and interviews to the locals. One of the important findings showed that the development of maritime tourism had positive impact on the local community, especially in providing business opportunities through Small Medium Enterprise (SME), and others. Accordingly, there is a need to ensure that the development of maritime tourism especially resorts on Pulau Perhentian will not affect the socioeconomic of the local community. This can be done through the development of sustainable tourism which had been introduced by the government.